The social, economic and environmental impact of an agroecological farming system: a case study in Phumulani Agri-village, Belfast, Mpumalanga, South Africa - Michael Rudolph; Mashford Zenda (Frontiers in Sustainable Food Systems)
This paper demonstrates the contribution of an agroecological model to food and nutrition security and livelihood strategies in the Phumulani Agri-village (PAV), located in Belfast, Mpumalanga, South Africa. PAV is a post-mining agri-village comprised of 32 households and approximately 200 individuals. The objectives of the project were to create jobs, generate income, establish a sustainable rural livelihood model that can be replicated, and implement environmentally friendly practices focusing on soil fertility, nutrition, green energy, and water security. A mixed research methodology was used to collect quantitative and qualitative data through structured questionnaires and focus group discussion. The Sustainable Livelihood Assets framework and Sustainable Development Goals (SDGs) were used to evaluate the project’s contributions. Ninety four percent of the thirty-two village household representatives and nine of the ten project beneficiaries completed questionnaires which were administered by the project manager. Findings after 24 months are based on our Sustainable Livelihood Assets framework and the Sustainable Development Goals (SDGs), show that the project has contributed to Economic Capital and SDGs 1 and 8, specifically addressing poverty, promoting decent work and economic growth by creating decent jobs and reliable income streams. The project also contributed to Human Capital and SDGs 2 and 3 through improved household food security and access to food. In addition, the intervention supported SDG Goal 4, Quality Education, through an integrated and accredited training and skills development programme. The initiative promoted Physical Capital and SDGs 6 and 7 by incorporating green infrastructure such as biogas digesters, a commercial wormery and boreholes with solar pumps. The findings confirm the effectiveness of agroecology in community and social development, demonstrating its positive social, economic, and environmental outcomes. The model can be replicated by government and corporate entities, potentially influencing policies and support programs that support agroecology in South Africa.